Bioenhanced degradation of toluene by layer-by-layer self-assembled silica-based bio-microcapsules - Lin, Hongyang; Yang, Yang; Li, Yongxia; Feng, Xuedong; Li, Qiuhong; Niu, Xiaoyin; Ma, Yanfei; Liu, Aijv (Frontiers in Microbiology, 2023)
In this study, micron-sized monodisperse SiO2 microspheres were used as sacrificial templates, and chitosan/polylactic acid (CTS/PLA) bio-microcapsules were produced using the layer-by-layer (LBL) assembly method. Microcapsules isolate bacteria from their surroundings, forming a separate microenvironment and greatly improving microorganisms’ ability to adapt to adverse environmental conditions. Morphology observation indicated that the pie-shaped bio-microcapsules with a certain thickness could be successfully prepared through LBL assembly method. Surface analysis showed that the LBL bio-microcapsules (LBMs) had large fractions of mesoporous. The biodegradation experiments of toluene and the determination of toluene degrading enzyme activity were also carried out under external adverse environmental conditions (i.e., unsuitable initial concentrations of toluene, pH, temperature, and salinity). The results showed that the removal rate of toluene by LBMs can basically reach more than 90% in 2 days under adverse environmental conditions, which is significantly higher than that of free bacteria. In particular, the removal rate of toluene by LBMs can reach four times that of free bacteria at pH 3, which indicates that LBMs maintain a high level of operational stability for toluene degradation. Flow cytometry analysis showed that LBL microcapsules could effectively reduce the death rate of the bacteria. The results of the enzyme activity assay showed that the enzyme activity was significantly stronger in the LBMs system than in the free bacteria system under the same unfavorable external environmental conditions. In conclusion, the LBMs were more adaptable to the uncertain external environment, which provided a feasible bioremediation strategy for the treatment of organic contaminants in actual groundwater.